STUDENT PREFERENCES ON TYPES OF LEARNING MODELS RELATED TO HUMAN AND OUTER SPACE MATERIALS - Susdarwono, Endro Tri (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
The method used in this research is experimental research. In general, the characteristics of experimental research in this study include: manipulation and observation. The type of research design used is pre experimental design, while data analysis uses analysis of variance through the two-way Friedman level. This method is applied to determine whether or not there are significant differences in values ​​in several population groups. By calculation, chi-squared value is 8.10. Because the value is greater than chi-square value in the table of 7.815, the null hypothesis is rejected and the alternative hypothesis is accepted. Thus, from the point of view of the learning model, it can be concluded that students have significant differences in preferences for the four learning models related to human and outer space materials. In this condition, the students considered that the four learning models had different levels of advantages and disadvantages in learning so that their preferences for the four were also different.